Aplicación de una auditoría informática para la empresa comercial almacenes Oña de la ciudad de Latacunga - Díaz Bedón, Freddy Mauricio (2006)
The “Application of a Computer Auditing by the Commercial Company “Almacenes Oña” in Latacunga city, based on the Methodology Cobit. It is an investigation carried out on the based of the handling of the computer resources that has in its different departments.The study universe is constituted by 3 managers, 9 workers and 127 costumers of the Almacenes Oña by the which select a model of 3 managers, 9 office workers and workers and 86 costumers.